ANALISIS AERODINAMIS SECARA TEORITIS DAN PENERAPAN APLIKASI INVENTOR DAN CFD PADA RANCANG BANGUN PROTOTYPE MOBIL LISTRIK “INKAS A6” BLDC 1000 WATT DENGAN KONSEP SHUTTLE GOLF - Jamaludin, Jamaludin; Efrizal, Efrizal; Ardian, M Arief Alfi; Hendrajit, Deco (Motor Bakar : Jurnal Teknik Mesin, 2024)
The more rapid development of the times in the era of globalization and technology, the use of transportation is the best solution to support increased human mobility. It is noted that the use of land transportation has increased along with the increase in human mobility. This matter was also followed by the existence of global issues regarding the energy crisis that hit the world. The need for transportation is increasing, resulting in an increase in the energy required.This final project report entitled "Theoretical Aerodynamic Analysis and Application of Inventor and CFD Applications in the Design and Build of the Electric Car Prototype "Inkas A6" Bldc 1000 Watt With the Golf Shuttle Concept" initial design and knowing airflow in the Shuttle golf vehicle simulation process carried out on the Autodesk CFD 2019 application The results of the simulations carried out with the Autodesk CFD 2019 software and the Cd (Coefficient Drag) calculations carried out by researchers on the body of this golf shuttle vehicle obtained a value of 34.3 and the maximum and minimum pressures obtained were 102683 Pa and 1013160 Pa. And for the value of the Drag Force calculation is 2367 Pa then the maximum and minimum relative airspeed obtained is 3.52 m/s and -1.06 m/s.